1991
DOI: 10.1007/bf00231851
|View full text |Cite
|
Sign up to set email alerts
|

Role of medial preoptic GABA neurones in regulating luteinising hormone secretion in the ovariectomised rat

Abstract: The role of GABA neurones in the medial preoptic area (MPOA) in regulating the activity of the luteinising hormone-releasing hormone (LHRH) neurones projecting to the median eminence was investigated in the conscious ovariectomised rat. Plasma luteinising hormone (LH) concentrations were measured while (1) endogenous GABA release from the MPOA was monitored with the technique of microdialysis, or (2) activity at the GABA receptor was modulated by local infusions into the MPOA. Microdialysis studies revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…Subsequent studies, however, have suggested that there may also be a nongenomic component to the action of P, possibly through P metabolites acting through the GABA A receptor (17). In rats, GABA has an inhibitory effect on GnRH (39) and LH secretion (40,41). GABA has also been implicated in LH inhibition in sheep (42) and specific manipulation of the GABA A , but not GABA B , receptor suppresses LH secretion (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies, however, have suggested that there may also be a nongenomic component to the action of P, possibly through P metabolites acting through the GABA A receptor (17). In rats, GABA has an inhibitory effect on GnRH (39) and LH secretion (40,41). GABA has also been implicated in LH inhibition in sheep (42) and specific manipulation of the GABA A , but not GABA B , receptor suppresses LH secretion (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showing that extracellular GABA concentrations in the supraoptic nucleus do not alter in response to suckling or individual milk ejections (Voisin, Chapman, Poulain & Herbison, 1994) suggests that the role of GABA may be permissive in nature and not involved directly in evoking each high frequency burst of firing. It is of interest to note that GABA has been hypothesized to play a very similar role to help generate pulsatile activity within the gonadotrophin-releasing hormone (GnRH) neurones; extracellular GABA concentrations do not change in relation to individual pulses of luteinizing hormone and both GABAA receptor agonists and antagonists infused into the immediate vicinity of the GnRH neurones inhibit pulsatile activity (Herbison, Chapman & Dyer, 1991). Together, these observations suggest that an on-going balance of GABA activity may be essential for the normal functioning of several neuroendocrine networks and we provide here such evidence for the magnocellular oxytocin neurones during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that in vivo the IAA y-aminobutyric acid (GABA) inhibits GnRH release by a mechanism residing in the POA, i.e. by an action at GnRH perikarya (Herbison et al 1991;Jarry et al 1991;Scott & Clarke, 1993). Pharmacological experiments with EAA agonists or antagonists prove the importance of EAA for both the regulation of pulsatile GnRH release and the induction of the pre-ovulatory LH surge (Lopez et al 1990;Ping et al 1994).…”
Section: MD Brown School Of Sport and Exercise Sciences University Omentioning
confidence: 99%